88-LB: Effects of Grape Skin Extract (GSE) on Glycemic Response to a Starch Challenge in Prediabetic Subjects - ALKASEM, MEIS; ABDALHAKAM, IBRAHEM; SULEIMAN, NOOR N.; ISKANDARANI, AHMAD NABIL; SAMRA, TAREQ A.; MIR, FAYAZ AHMAD; MOHAMMAD, RAMZI M.; ABOU-SAMRA, ABDUL-BADI; ZHOU, KEQUAN; SKARULIS, MONICA C. (Diabetes (New York, N.Y.), 2019)
Prediabetes is a condition leading to increased risk of diabetes and its complications and cardiovascular disease. Annually, ∼10% prediabetic subjects progress to T2D. We, and other investigators, reported that grape skin extract (GSE) impacts postprandial glycemia through alpha glucosidase inhibition. This study aims to examine the effect of GSE on glycemic response to a starch challenge in healthy prediabetic subjects. The study was approved by the IRB of Hamad Medical Corporation. Subjects were screened from a high-risk population based on family history and/or fasting glucose (5.7-7.3 mmol) and IGT confirmed with 75 gram OGTT. Subjects were randomized to GSE capsule 600 (N=4), 1200 (N=8), 1800 (N=15) or 2400 mg (N=14). Each received a meal of 35 gram (uncooked weight) rice with or without the assigned dose of GSE and blood glucose was measured at time 0, 15, 30, 60 and 120 minutes. Area under the curve (AUC) was calculated using the trapezoidal method and the subjects were classified into “responders” or “non-responders” if AUC after GSE was reduced by at least 1 SD. A total of 41 eligible subjects (83% male; age 29±8 years; BMI 23.2%±5.9, 34% Arab, 24% African, 17% Asian, 24% Indian) with prediabetes were enrolled. A total of 4 (9.7%)subjects decreased AUC by 2SD; 24% decreased by 1 SD and the remainder had no positive response to a single dose of GSE. There were no responders to 600 mg; 2 in 1200 mg; 4 in 1800 mg; and 3 in 2400 mg dose. There were no differences between the responders and non-responders in clinical or biochemical characteristics. In conclusion, 24% of prediabetic subjects had a positive response to GSE in a starch challenge test. The value of the test in characterizing prediabetic subjects who may benefit from GSE to reverse their prediabetic condition is currently under further investigation. In Qatar, the prevalence of diabetes is 17% and expected to increase. Studies to develop natural products to prevent diabetes are of great public health interest.